2008
DOI: 10.1111/j.1365-3059.2007.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora alni causing decline of black and grey alders in the Czech Republic

Abstract: Bleeding canker and decline of riparian alder populations has been an important problem in many European countries, including the Czech Republic. Initially, an 'alder Phytophthora ' was isolated from damaged black alder trees in western Bohemia near the town of Karlovy Vary in 2001 ( d ern y et al ., 2003). The exact species identification was unknown at this time. Since its original discovery, we have isolated similar Phytophthora species from damaged innerbark and conductive tissues of declining trees of Aln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…In 2006, the pathogen was known to be present in about 60 sites and to be spreading rapidly, particularly in the western part of the Czech Republic (Cerny et al 2008). The loss of trees in affected areas has increased enormously: tens of thousands of alder trees have disappeared to date in the area of the Upper Vltava River Authority alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2006, the pathogen was known to be present in about 60 sites and to be spreading rapidly, particularly in the western part of the Czech Republic (Cerny et al 2008). The loss of trees in affected areas has increased enormously: tens of thousands of alder trees have disappeared to date in the area of the Upper Vltava River Authority alone.…”
Section: Resultsmentioning
confidence: 99%
“…In morphological studies ten selected isolates were examined. In a previous study, DNA sequences of the ITS region of two of these isolates (GenBank accession numbers EF194776 and EF194777) were compared with sequences available from the GenBank (Cerny et al 2008). One isolate has been deposited in the Culture Collection of Fungi, Prague, under No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was likely that this decline was connected to the flooding that occurred in 2002 (Vyhlídková et al 2005) because the increased water level and flooding could damage the alders and induce morphological changes as seen by McVean (1956). The dangerous pathogen of alders Phytophthora alni has been spreading rapidly in alder stands, particularly in the western part of the Czech Republic in recent years, and has leading to significant losses in highly affected stands (Cerny et al 2008). We felt it important to distinguish which of these factors was the real cause of the decline.…”
mentioning
confidence: 99%
“…Gibbs et al 1999;Szabó et al 2000;Streito et al 2002;Oszako, Orlikowski 2005) and has caused a devastating epidemic in alders. In the Czech Republic, the pathogen was first isolated from damaged black alder trees in Western Bohemia in 2001 (Černý et al 2003) but was properly identified only later (Cerny et al 2008). To date, the pathogen has been found in approximately 150 sites, although the disease symptoms have been detected in approximately 300 sites throughout the Czech Republic.…”
mentioning
confidence: 99%